Fermentation, stability and degradability of whole-crop oat silage ensiled with a commercial inoculant - Pienaar, Johanni (Stellenbosch : Stellenbosch University, 2010)
Thesis (MScAgric (Animal Sciences))--Stellenbosch University, 2010.